Evaluation of the Variability of Parameters of the Financial Status of the Republic of Belarus in 2000-2020 - V. V. Skrund (Цифровая трансформация)
Based on the analysis of national and foreign scientific literature, the paper determines the main parameters of financial stability at the macro level, taking into account the characteristics of the economy of the Republic of Belarus. These parameters include the level of inflation, exchange rates, the level of dollarization of the economy, interest rate, the balance of external trade, the state of the economic entities' finances, as well as financial soundness indicators developed by the International Monetary Fund. The quantitative assessment of the inter-linkages between these parameters was carried out: a correlation matrix and regression models are constructed. The study used official statistical information published by the National Bank and the National Statistical Committee of the Republic of Belarus on a monthly, quarterly and annual basis for 2000-2019.